Targeted Protein Degradation by KLHDC2 Ligands Identified by High Throughput Screening - Zhou, Han; Zhou, Tongliang; Yu, Wenli; Liu, Liping; Ko, Yeonjin; Johnson, Kristen A; Wilson, Ian A; Schultz, Peter G; Bollong, Michael J (eLife Sciences Publications, 2025)
Proteolysis targeting chimeras (PROTACs) enable the selective and sub-stoichiometric elimination of pathological proteins, yet only two E3 ligases are routinely used for this purpose. Here, we expand the repertoire of PROTAC compatible E3 ligases by identifying a novel small molecule scaffold targeting the ubiquitin E3 ligase KLHDC2 using a fluorescence polarization-based high throughput screen. We highlight the utility of this ligand with the synthesis of PROTACs capable of potently degrading BRD4 in cells. This work affords additional chemical matter for targeting KLHDC2 and suggests a practical approach for identifying novel E3 binders by high throughput screening.